Altered MicroRNA Maturation in Ischemic Hearts: Implication of Hypoxia on XPO5 and DICER1 Dysregulation and RedoximiR State - Lorena Pérez-Carrillo; Isaac Giménez-Escamilla; María García-Manzanares; Juan Carlos Triviño; Sandra Feijóo-Bandín; Alana Aragón-Herrera; Francisca Lago; Luis Martínez-Dolz; Manuel Portolés; Estefanía Tarazón; Esther Roselló-Lletí (MDPI AG, 2023)
Ischemic cardiomyopathy (ICM) is associated with abnormal microRNA expression levels that involve an altered gene expression profile. However, little is known about the underlying causes of microRNA disruption in ICM and whether microRNA maturation is compromised. Therefore, we focused on microRNA maturation defects analysis and the implication of the microRNA biogenesis pathway and redox-sensitive microRNAs (redoximiRs). Transcriptomic changes were investigated via ncRNA-seq (ICM, n = 22; controls, n = 8) and mRNA-seq (ICM, n = 13; control, n = 10). The effect of hypoxia on the biogenesis of microRNAs was evaluated in the AC16 cell line. ICM patients showed a reduction in microRNA maturation compared to control (4.30 ± 0.94 au vs. 5.34 ± 1.07 au, p ˂ 0.05), accompanied by a deregulation of the microRNA biogenesis pathway: a decrease in pre-microRNA export (XPO5, FC = −1.38, p ˂ 0.05) and cytoplasmic processing (DICER, FC = −1.32, p ˂ 0.01). Both processes were regulated by hypoxia in AC16 cells (XPO5, FC = −1.65; DICER1, FC = −1.55; p ˂ 0.01; Exportin-5, FC = −1.81; Dicer, FC = −1.15; p ˂ 0.05). Patients displayed deregulation of several redoximiRs, highlighting miR-122-5p (FC = −2.41, p ˂ 0.001), which maintained a good correlation with the ejection fraction (r = 0.681, p ˂ 0.01). We evidenced a decrease in microRNA maturation mainly linked to a decrease in XPO5-mediated pre-microRNA export and DICER1-mediated processing, together with a general effect of hypoxia through deregulation of biogenesis pathway and the redoximiRs.